CSF N‐glycan profile reveals sialylation deficiency in a patient with GM2 gangliosidosis presenting as childhood disintegrative disorder. Issue 4 (19th August 2015) - Barone, Rita; Sturiale, Luisella; Fiumara, Agata; Palmigiano, Angelo; Bua, Rosaria O.; Rizzo, Renata; Zappia, Mario; Garozzo, Domenico
Abstract : Protein N‐glycosylation consists in the synthesis and processing of the oligosaccharide moiety (N‐glycan) linked to a protein and it serves several functions for the proper central nervous system (CNS) development and function. Previous experimental and clinical studies have shown the importance of proper glycoprotein sialylation for the synaptic function and the occurrence of autism spectrum disorders (ASD) in the presence of sialylation deficiency in the CNS. Late‐onset Tay Sachs disease (LOTSD) is a lysosomal disorder caused by mutations in the HEXA gene resulting in GM2‐ganglioside storage in the CNS. It is characterized by progressive neurological impairment and high co‐occurrence of psychiatric disturbances. We studied the N‐glycome profile of the cerebrospinal fluid (CSF) in a 14 year‐old patient with GM2‐gangliosidosis (LOTSD). At the age of 4, the patient presented regressive autism fulfilling criteria for childhood disintegrative disorder (CDD). A CSF sample was obtained in the course of diagnostic work‐up for the suspicion of an underlying neurodegenerative disorder. We found definite changes of CSF N‐glycans due to a dramatic decrease of sialylated biantennary and triantennary structures and an increase of asialo‐core fucosylated bisected N‐glycans. No changes of total plasma N‐glycans were found. Herein findings highlight possible relationships between the early onset psychiatric disturbance featuring CDD in the patient and defective protein sialylation in the CNS. In conclusion, the study first shows aberrant N‐glycan structures of CSF proteins in LOTSD; unveils possible pathomechanisms of GM2‐gangliosidosis; supports existing relationships between neuropsychiatric disorders and unproper protein glycosylation in the CNS. Autism Res 2016, 9: 423–428 . © 2015 International Society for Autism Research, Wiley Periodicals, Inc.